Thermal performance of carbon-based microencapsulated phase change materials - Abdullah, Adli Zil Ikram; Abdollah, Mohd Fadzli bin; Tee, Boon Tuan; Amiruddin, Hilmi; Mat Yamin, Ahmad Kamal; Tamaldin, Noreffendy (2015)
The aim of this study is to investigate the effect of carbon-based materials for the thermal performance of microencapsulated phase change material (µPCM). The sample was prepared separately by mixing 5 wt.% of Multiwall Carbon Nanotube (MWCNT) and 5 wt.% Expanded Graphite (EG) with µPCM using a powder metallurgy technique. The mixed powder was then compacted into a disc with a diameter of 45 mm and thickness of 5 mm using a hot compaction technique. The thermal performance was tested according to the ASTM standard. It was found that the addition of MWCNT into µPCM can absorb heat effectively as compared to pure µPCM and µPCM/EG composite.